Analysis of genes that are differentially expressed during the Sclerotinia sclerotiorum–Phaseolus vulgaris interaction - Oliveira, Marília B.; de Andrade, Rosângela V.; Grossi-de-Sá, Maria F.; Petrofeza, Silvana (Frontiers in Microbiology, 2015)
The fungus Sclerotinia sclerotiorum (Lib.) de Bary, one of the most important plant pathogens, causes white mold on a wide range of crops. Crop yield can be dramatically decreased due to this disease, depending on the plant cultivar and environmental conditions. In this study, a suppression subtractive hybridization (SSH) cDNA library approach was used for the identification of pathogen and plant genes that were differentially expressed during infection of the susceptible cultivar BRS Pérola of Phaseolus vulgaris L. A total of 979 unigenes (430 contigs and 549 singletons) were obtained and classified according to their functional categories. The transcriptional profile of 11 fungal genes related to pathogenicity and virulence were evaluated by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR). Additionally, the temporal expression profile obtained by RT-qPCR was evaluated for the following categories of plant defense-related genes: pathogenesis-related genes (PvPR1, PvPR2, and PvPR3), phenylpropanoid pathway genes (PvIsof, PvFPS1, and 4CL), and genes involved in defense and stress-related categories (PvLox, PvHiprp, PvGST, PvPod, and PvDox). Data obtained in this study provide a starting point for achieving a better understanding of the pathosystem S. sclerotiorum–P. vulgaris.